Formation of Lutein, β-Carotene and Astaxanthin in a Coelastrella sp. Isolate - Hamdy Elsayed Ahmed Ali; Fritz Vorisek; Scot E. Dowd; Stephanie Kesner; Yang Song; Dali Qian; Mark Crocker (Molecules, 2022)
In this study, the effect of media composition, N/P ratio and cultivation strategy on the formation of carotenoids in a Coelastrella sp. isolate was investigated. A two-stage process utilizing different media in the vegetative stage, with subsequent re-suspension in medium without nitrate, was employed to enhance the formation of carotenoids. The optimal growth and carotenoid content (β-carotene and lutein) in the vegetative phase were obtained by cultivation in M-8 and BG11 media. Use of a N/P ratio of 37.5 and low light intensity of 40 μmol m−2 s−1 (control conditions) led to optimal biomass production of up to 1.31 g L−1. Low concentrations of astaxanthin (maximum of 0.31 wt. %) were accumulated under stress conditions (nitrogen-deficient medium containing 1.5 % of NaCl and light intensity of 500 μmol m−2 s−1), while β-carotene and lutein (combined maximum of 2.12 wt. %) were produced under non-stress conditions. Lipid analysis revealed that palmitic (C16:0) and oleic (C18:1) constituted the main algal fatty acid chains (50.2 ± 2.1% of the total fatty acids), while esterifiable lipids constituted 17.2 ± 0.5% of the biomass by weight. These results suggest that Coelastrella sp. could also be a promising feedstock for biodiesel production.